Green tea and the risk of prostate cancer: A systematic review and meta-analysis - Guo, Yuming (Medicine (Baltimore), 2017)
Prostate cancer (PCa) now remains the 2nd most frequently diagnosed cancer. In recent years, chemoprevention for PCa becomes a possible concept. Especially, many phytochemicals rich foods are suggested to lower the risk of cancer. Among these foods, green tea is considered as effective prevention for various cancers. However, clinical trials and previous meta-analyses on the relationship between green tea consumption and the risk of PCa have produced inconsistent outcomes. This study aims to determine the dose–response association of green tea intake with PCa risk and the preventive effect of green tea catechins on PCa risk. Seven observational studies and 3 randomized controlled trials were retrieved from Cochrane Library, PubMed, Sciencedirect Online, and hand searching. The STATA (version 12.0) was applied to analyze the data. The relative risks (RRs) and 95% confidence intervals were pooled by fixed or random effect modeling. Dose–response relations were evaluated with categories of green tea intake. Although there was no statistical significance in the comparison of the highest versus lowest category, there was a trend of reduced incidence of PCa with each 1 cup/day increase of green tea (P = 0.08). Our dose–response meta-analysis further demonstrated that higher green tea consumption was linearly associated with a reduced risk of PCa with more than 7 cups/day. In addition, green tea catechins were effective for preventing PCa with an RR of 0.38 (P = 0.02). In conclusion, our dose–response meta-analysis evaluated the association of green tea intake with PCa risk systematically and quantitatively. And this is the first meta-analysis of green tea catechins consumption and PCa incidence. Our novel data demonstrated that higher green tea consumption was linearly reduced PCa risk with more than 7 cups/day and green tea catechins were effective for preventing PCa. However, further studies are required to substantiate these conclusions.